METODE PENANAMAN NILAI-NILAI MULTIKULTURAL PADA SISWA KELAS RENDAH (STUDI PADA MI DI MWCNU LP. MAARIF KRAKSAAN) - Imam Bukhori (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2018)
The purpose of the research is to describe the methods of multicultural values implanting for early students in madrasah ibtidaiyahs on MWCNU LP Ma’arif Kraksaan subdistrict. The method that used to succeed the implanting of multicultural values are story telling, playing, study tour, inuring, modelling and reading poems. The most used method is story telling and inuring. The using of those methods are to give mutual understanding for the multicultural values such as openness, humanity, tolerance, mutually help, justness, equality and brotherhood, good thought, and have a great affection to the nation. By using those methods, the students behaviour could be changeable from refusing the others that differents become accepting and friendly with the others.  The constrains also appear while impalnting multicultural values, such as the lack of knowledge in story telling techniques media used by teachers, the inconsistency of posture in school and the circumstances where the students live.